(untitled) - Hoston, Germaine A. (Princeton, N.J., 1986)
Indiana University This study, the first of its kind in English, is a comprehensive analysis of the Marxist debate in Japan over how capitalism developed in that country. Germaine A. Hoston clearly demonstrates the originality of Japanese Marxist scholars and political leaders and the importance of their thought to the Marxist and non-Marxist discourse on political development.
Keywords: Communism,Chủ nghĩa cộng sản; History,Lịch sử; 20th century,Thế kỷ 20; Japan,Nhật Bản